Cellular and structural insight into dynamin function during endocytic vesicle formation: a tale of 50 years of investigation. Issue 11 (10th November 2022) - Perrais, David
Abstract: Dynamin is one of the major proteins involved in endocytosis. First identified 50 years ago in a genetic screen in Drosophila melanogaster, it has become a central player in many forms of endocytosis, such as clathrin-mediated endocytosis or synaptic vesicle endocytosis, as well as other important cellular processes such as actin remodelling. Decades of work using biochemical and structural studies, cell-free assays, live cell imaging, acute inhibition and genetic studies have led to important insights on its mode of action. Dynamin is a remarkable mechano-GTPase, which can do a lot to membranes on its own but which is, in cells, at the centre of a vast protein and lipid network and cannot work in isolation. This review summarizes the main features of dynamin structure and function and its central role in membrane remodelling events, and give an update on the latest results.